Mechatronic System for Tocosh Fermentation: Design, Automation and Quality Improvement - Valero Gomez, Sebastian Kevin (2024)
This research presents a comprehensive approach to the design, control, and structure of an innovative fermentation machine for the production of Tocosh from potato fermentation. In order to achieve this objective, a thorough analysis of the various crucial parameters involved in the fermentation process has been carried out. The main objective of the design proposal is the real-time monitoring of essential factors such as pH and temperature in the process. To achieve this, a control system has been designed that will allow precise and constant monitoring of the temperature and pH parameters, and monitoring of the water level was also carried out to improve the quality of the product. Furthermore, the structural analysis of the fermentation chamber is addressed in detail, using Inventor software for the creation of three- dimensional models of each component and for the generation of the final design. It was revealed that the current fermentation process is based on empirical methods, involving the exposure of potatoes in areas close to lagoons or rivers for a period of between 4 and 24 months. This process lacks adequate control over the fundamental factors for successful fermentation, such as pH and temperature. Through this preliminary analysis, essential data has been collected to support the design and implementation of an innovative prototype fermentation chamber. The present study represents a significant step towards the optimization and modernization of the Tocosh production process, with the perspective of improving the quality and efficiency of this ancient method of food preservation.